IVAN VASILIEVICH SAVCHENKO IS 70 - V. F. Pivovarov; O. N. Pishnaya (Овощи России, 2012)
October 8, 2012 is the 70th anniversary of the vice-president, academician, PhD of RAAS Ivan Savchenko. Throughout his life I.V. Savchenko devoted himself to science. During his professional background he has been a student at Moscow State University, a graduate student, senior researcher, Head of the laboratory of geobotany of Feed Institute and a vice president of RAAS.